Pengaruh Pemanfaatan, Dan Efisiensi Waktu, dan Kemudahan Terhadap Keputusan Penggunaan E-Wallet GOPAY - Erlangga, Riki; Ferdiansyah, Muhammad Tri; salma, Putri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to evaluate the impact of Usefulness, Time Efficiency, and Convenience on the choice to use the digital wallet application GoPay in Sukarame, both individually and collectively. The research sample consisted of 100 respondents aged 17 to 40, selected through incidental sampling. Data were gathered using a Google Form questionnaire and analyzed with SPSS version 19. The results of the t-test indicate that all three variables have a significant individual effect on the decision to use GoPay. An R Square value of 0. 731 reveals that 73% of the decision to use is influenced by the variables of Usefulness, Time Efficiency, and Convenience, while 27% is influenced by other factors. The study concludes that GoPay is competitive with other digital wallets and that these three variables have a significant collective impact on the decision to use GoPay in Sukarame.